Environmental Burden of Diarrhoeal Diseases due to Unsafe Water Supply and Poor Sanitation Coverage in Nepal - Aryal, K K; Joshi, H D; Dhimal, M; Singh, S P; Dhimal, B; Dhakal, P; Bhusal, C L (Journal of Nepal Health Research Council, 2012)
Background: Unsafe water and poor sanitation are major contributing factors of diarrhoea. Most of the water supply systems in urban and rural area of Nepal do not have basic water treatment facilities. This has resulted in frequent reports of fecal contamination in drinking water and outbreaks of waterborne diseases. The purpose of this study was to find out the burden of diarrhoeal diseases at different scenario of water supply system and sanitation status in Nepalese context. Methods: A cross-sectional study was conducted in four different districts of Nepal analyzing six different scenarios based on availability of water supply and sanitation status. Village Development Committees (VDCs) and community selection was made purposively and 360 households, 60 from each scenario were selected conveniently to achieve the required number. Within the selected household, the head of the household or any member above 18 years of age was interviewed using a structured questionnaire. Observation was done for toilet and water sources besides questionnaire method. Results: Incidence of diarrhoea per 1000 population was found to be the highest in scenario-IV (Spring without toilet) with 204.89 followed by scenario-VI (Tube well without toilet) with 145.30, while it was less in scenario-I (Tap water with toilet) with 46.05. Accordingly, the burden of disease (YLD) was also found to be the highest in scenario-IV and the lowest in scenario-I. Most of the households didn’t treat water before drinking. Hand washing practice was found to be more than 90% regardless of toilet availability. Conclusions: The greater risk of acquiring diarrhoeal disease and higher burden of disease in situation of unprotected water source and absence of toilet shows that these are still important contributing factors for diarrhoeal disease in Nepal. Use of sanitary toilets and protected water source are the important measures for diarrhoeal disease prevention in Nepal. Keywords: diarrhoeal disease; environmental burden of disease; water supply and sanitation; scenario.